2018
DOI: 10.2478/humo-2014-0008
|View full text |Cite
|
Sign up to set email alerts
|

The anthropometric characteristics of futsal players compared with professional soccer players

Abstract: Purpose. The aim of the study was to compare the morphological characteristics of experienced futsal players with professional soccer players. Methods. The research sample included 22 university futsal players and 22 professional soccer players. Parameters including body height and mass, skinfold thicknesses of the trunk and extremities, lower limb length, trunk width, humerus and femur bone breadths, and the circumferences of the chest, hips, thighs, and calves were used to calculate various somatic indices. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 22 publications
1
11
0
2
Order By: Relevance
“…Thus, in our study, we did not have to consider the body type structure during the analysis of the obtained data (Corrêa, Davids, & Tani, 2014). In addition, the data we received confirmed previous results from other researchers that were related to the peculiarities of the body structure of the futsal players with different positional roles (Burdukiewicz, Pietraszewska, & Goliński, 2014;Iedynak, Galamandjuk, & Сhopik, 2017). In addition, during a competitive activity, the largest energy expenditure was exhibited by the defenders, and the pivots and goalkeepers exhibited almost identical energy expenditures.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Thus, in our study, we did not have to consider the body type structure during the analysis of the obtained data (Corrêa, Davids, & Tani, 2014). In addition, the data we received confirmed previous results from other researchers that were related to the peculiarities of the body structure of the futsal players with different positional roles (Burdukiewicz, Pietraszewska, & Goliński, 2014;Iedynak, Galamandjuk, & Сhopik, 2017). In addition, during a competitive activity, the largest energy expenditure was exhibited by the defenders, and the pivots and goalkeepers exhibited almost identical energy expenditures.…”
Section: Discussionsupporting
confidence: 87%
“…The information about the energy expenditure of each futsal team player has a practical value because it will help trainers with their training activities. Energy expenditure of players is due to many reasons (Kagawa, Kobata, & Nakamura, 2014;Burdukiewicz, Pietraszewska, & , Goliński, 2014). Our study showed that all players belonged to the same body type structure, namely ectomorph.…”
Section: Discussionmentioning
confidence: 48%
“…Overall, the futsal players under study were shorter and lighter that nontraining students and soccer players. burdukiewicz et al [3] revealed no significant differences in body build between futsal players and professional soccer players. The results of the present study do differ from those obtained by other authors.…”
Section: Resultsmentioning
confidence: 99%
“…The general model of the players' morphological characteristics varies depending on their pitch position, which is related to the performance of different activities [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Introduction 1 Football is a game in which anthropometric characteristics are important factors for specific gaming positions [1]. Morphological characteristics [2,3] successfully distinguish footballers compared to the competitive level and the game position [4] and they are important factors in selecting players in team sports [5,6] describing the structure of the body of the player based on a large number of anthropometric data [7], which define the longitudinal and transversal dimensionality of the skeleton, mass and volume of the body [8] and they are under great influence of endogenous and exogenous factors [9]. In many studies it has been confirmed that the morphological characteristics of athletes can influence the success in achieving sports results [10,11].…”
mentioning
confidence: 99%